WORKSHOP ONLINE: METODE SYSTEMATIC LITERATURE RIVIEW SEBAGAI ALTERNATIF KARYA ILMIAH AKHIR BAGI MAHASISWA DAN DOSEN DI MASA PANDEMI COVID-19 - Edi Susanto; Arief Irfan Syah Tjaja; Hari Adianto; Ghifari Hamzah; Rispianda Rispianda (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2021)
The aim of community service (PKM) is to provide alternative solutions for final year students and lecturers at PKM partners, by introducing systematic literature review (SLR) research methods for final scientific works through online workshop amid the impact of the Covid-19 pandemic. With strict social distancing rules and a work from home (WFH) policy that limits/experiences difficulties in making student theses to conduct field research. Problems that exist with partners also have an impact on delays in final scientific works preparation, while the preparation of final scientific papers is an obligation as a requirement for graduation, other things also have an economic impact due to the spread of layoffs for students' families/ guardians, and business activities are also not easy with the PSBB regulation from the government through a circular, with restrictions on offline learning activities/ data collection in the field. Meanwhile, PKM partners also do not know the SLR method, so it is necessary to have an SLR method workshop as an alternative solution for conducting research using secondary data so that the research method policy can be an alternative solution. The evaluation of PKM activities is carried out with a pre-test at the beginning and a post-test at the end of the workshop. Evaluation results of participants on average increased from the previous 49 to 82 or an increase of about 59%. This means that, in general, this training was successful because it exceeded the indicator requirements, namely an average score of >75.